To complete the square follow these steps:
First, get the unit coefficient (5) out of the way, by subtracting 5 from both sides:
x^2 - 12x = -5
Now take the x term coefficient (-12), halve it (-6) and square it (36). This is the number you need to add to both sides:
x^2 - 12x + 36 = 31
Now the left hand side can be written as a perfect square:
(x - 6)^2 = 31
Now you can take the square root of both sides and solve for x:
x-6 = sqrt(31)
or
x-6 = -sqrt(31)
So x = 6 +/- sqrt(31)
2007-01-07 16:38:15
·
answer #1
·
answered by Puzzling 7
·
1⤊
2⤋
get rid of 5 on both sides
so that you get this (x^2)-12x = -5
divide the x variable which is 12 by 2 so you get six
2 (square) the 6 so you get 36
add 36 on both sides
so you get ,
(x^2)-12x+36 = 31
then you simplify and finish the problem which comes out too.....
(x-6)^2 = 31
2007-01-07 16:40:26
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
1x^2-12x+5 = 0
b"2-4ac = 12"2-4*1*5 = 124
x = (-(-12)+- sqrt( 12^2 -4*1*5 ))/(2*1)
x = (-(-12)+- sqrt( 124 ) )/(2*1)
6+- sqrt( 31)
its been a few years i had to take a refresher look at the web page
2007-01-07 17:09:41
·
answer #3
·
answered by texasbar 3
·
0⤊
1⤋
subtract 5 on both sides
looks like (x^2)-12x = -5
divide the x variable (12) by two so you get 6
square the 6 so you get 36
add 36 on both sides
looks like:
(x^2)-12x+36 = 31
simplify:
(x-6)^2 = 31
2007-01-07 16:35:55
·
answer #4
·
answered by sir_camm 3
·
0⤊
2⤋
x^2 - 12x + 5 = 0
x^2 - 12x = -5
x^2 - 12x + 36 = 31
(x - 6)^2 = 31
x - 6 = sqrt(31)
x = 6 ± sqrt(31)
2007-01-07 16:34:12
·
answer #5
·
answered by Sherman81 6
·
1⤊
2⤋
Add: (b/2)^2 to both sides: (-12/2)^2 = (-6)^2 = 36
2007-01-07 16:35:30
·
answer #6
·
answered by S. B. 6
·
0⤊
2⤋